Association of Smokeless Tobacco with Coronary Heart Diseases - Ahmad, Jamil; Pasha, AKM Mustafa Kamal; Islam, Md Ziaul; Kabir, SM Humayan (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Coronary heart diseases (CHDs) are one of the leading killers in our country. Both smoking and smokeless tobacco (SLT) are major risk factors for CHDs. Bangladesh is one of the top-ranked countries in the world regarding SLT users. Objectives: To determine the relation between smokeless tobacco uses and CHDs. Materials and Methods: This case-control observational study was conducted at the outpatientdepartment of Combined Military Hospital, Dhaka and National Institute of Cardiovascular Diseases and Hospital from July 2017 to June 2018 among selected 62 adultcoronary heart diseasepatients (Cases) and 62 age and sex-matched non-CHDs patients (Controls). Results: In Cases; 61.3% of respondents were male and mean age was 51.56 + 11.46 years. In Controls; 56.5 % respondents were male and mean age was 48.15 ± 12.53 years. Among the CHDs cases 19 (30.6%) was SLT users but in non-CHD cases it was only 10(16.1%) and this difference was not statistically significant. All the SLT users in CHDs Controlswere longduration users and majority uses Gul or Jorda. Conclusion: Number of SLT users was more in CHDs Cases than non-CHD Controls but this difference was not statistically significant. Further studies with more sample size are recommended to find the relation between SLT users and CHDS. Journal of Armed Forces Medical College Bangladesh Vol.14 (2) 2018: 106-108